Ethical Draft Preparation of Boarding House Residents in Mulyoagung Village in the New Normal Era - Fitria Esfandiari (Jurnal Dedikasi Hukum, 2021)
The Covid 19 pandemic in all parts of the world has led to a shift in the normal life order into one in the new normal era. The city of Malang, as one of the centers of education in East Java, is one of the destinations for migrants from outside the city to study, work and live either for a long time or temporarily. In general, these migrants came from various regions in Indonesia and had various social, economic, and political backgrounds. More specifically, Mulyoagung Village is one of the villages in Malang Regency, East Java, whose population is very heterogeneous and close to education centers, both Islamic boarding schools, and universities. The problems raised in this service are, first, efforts to assist the drafting of boarding house ethics in RT 04 RW 10 Dusun Jetis Mulyoagung Village in the New Normal Era. Second, the problem of implementing the implementation of health protocols in the RT 04 RW 10 Dusun Jetis Mulyoagung Village to boarding houses. The service methods used are, First, assisting in drafting boarding house ethics in the new normal era. Second, socialization to the public via radio. The results of the assistance carried out by the service provider formulated ten questionnaire questions to explore the problems faced by boarding houses, including those related to environmental management in terms of security, order, cleanliness, and administrative order for boarding residents who come from outside the region. Also, there are facilities and infrastructure that support the implementation of health protocols, such as handwashing facilities. There has been awareness among residents regarding the implementation of health protocols. As the output of this activity, the publication of scientific articles in dedication journals is compiled. Pendampingan Penyusunan Draft Etika Warga Boarding House di Desa Mulyoagung di Era New Normal. Pandemi Covid 19 di seluruh belahan dunia menyebabkan beralihnya tatanan hidup normal menjadi tatanan di era new normal. Kota Malang sebagai salah satu pusat pendidikan di Jawa Timur menjadi salah satu tujuan bagi pendatang dari luar kota ini untuk studi, bekerja maupun tempat tinggal baik untuk jangka waktu lama ataupun sementara waktu. Pada umumnya pendatang ini berasal dari berbagai wilayah di Indonesia dan berlatar belakang sosial, ekonomi dan politik dan beragam. Lebih spesifik Desa Mulyoagung adalah salah satu desa di Kabupaten Malang Jawa Timur yang penduduknya sangat heterogen dan dekat pusat-pusat pendidikan, baik pesantren maupun perguruan tinggi. Problematika yang diangkat dalam pengabdian ini yakni ini pertama, upaya pendampingan penyusunan draft etika warga Boarding House di lingkungan RT 04 RW 10 Dusun Jetis Desa Mulyoagung di Era New Normal. Kedua, problematika penerapan upaya penerapan protokol kesehatan di lingkungan RT 04 RW 10 Dusun Jetis Desa Mulyoagung terhadap warga Boarding House. Metode pengabdian yang digunakan yaitu, Pertama, melakukan pendampingan dalam penyusunan draft etika warga Boarding House di era new normal. Kedua, sosialisasi kepada masyarakat melalui radio. Hasil pendampingan yang dilakukan pengabdi merumuskan 10 pertanyaan kuisioner untuk menggali problematika yang dihadapi oleh warga Boarding House diantaranya yakni terkait tata kelola lingkungan sekitar baik dari aspek keamanan, ketertiban, kebersihan maupun tertib administrasi bagi warga Boarding House yang berasal dari luar daerah. Selain itu sudah tersedianya  sarana dan prasarana yang mendukung penerapan protokol kesehatan semisal sarana cuci tangan. Telah timbul kesadaran di lingkungan warga terkait penerapan protokol kesehatan.  Sebagai luaran kegiatan ini yaitu disusunnya publikasi artikel ilmiah di jurnal pengabdian.